A remarkable new species of Hypogastrura (Collembola, Hypogastruridae) from the Romanian Carpathians - Paśnik, Grzegorz; Sternalski, Jakub (Zootaxa, 2021)
A new species of Hypogastrura from the Romanian Carpathians is described and illustrated. The new species is characterised by unique combination of morphological characters: presence of seven ocelli, the antennal segment IV with 4 thin, cylindrical sensilla, the presence of 5 setae on ventral tube, the short anal spines situated on high papillae and distinct chaetotaxy. The species is not easy to classify in the present system of the generic subdivision. Considering the presence of only 7+7 ocelli, the new species can be compared only with H. pyrenaica (Cassagnau, 1959), while in other morphological features it is similar to H. aterrima Yosii, 1972 and H. tethyca Ellis, 1976. The similarity between these species and systematic position of the new species are discussed.